RUMAH KUMPUL LANSIA DI KABUPATEN BANJAR - Fadli, Muhammad; Hartono, Rudi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
An elderly person is someone who is aged 60 years old or above. The Central Bureau of Statistics projects that the number of elderly people will reach one-fifth (19.90%) of Indonesia's total population in 2045. This increase brings problems to the elderly themselves in the form of decreased body function due to the aging process. Rumah Kumpul Lansia is a solution to help the elderly to get professional services and care in their daily lives. The behavioral architecture approach method was chosen to observe the behavior of the elderly to produce a building that suits the character and mindset of the elderly. The result is the concept of "Manoewa" which is able to answer the problems of independence, productivity, health, and insight among elderlies.